Clinical, biochemical and histological changes during developement of pregnancy ketosis in goats - Amirul, F. M. A.; Md. Ajat, Mohd Mokrish; Lai, Kok Song; Saad, Mohd Zamri; Abu Bakar @ Zakaria, Md Zuki; Abu Hassim, Hasliza (Veterinary Association Malaysia, 2016)
Thin does or very over-conditioned does and does carrying with multiple pregnancies are more likely to develop pregnancy ketosis (pregnancy toxaemia). Pregnancy ketosis is one of the metabolic disorders in ruminant animal such as does and ewes during the last weeks of pregnancy (5 – 6 weeks before gestation) and beside high ketone body levels characterised by free fatty acids levels (FFA). These FFA are derived from the adipose tissue. The ability of adipocytes to respond to changes in the energy balance, by secretion of FFA makes this parameter a main indicator for disorder that coincide with changes in energy balance. It is biochemically and endocrinologically characterized by ketosis, hypoinsulinemia and an elevation of B- hydroxybtyrate concentration in the plasma, free fatty acids (FFA), and cortisol. However, the effect of plasma free fatty acid on pathophysiology, metabolites and histological changes of this disorder remain poorly understood. Clinical signs, often with a slow onset, are characterised by neuorological signs like teeth grinding, stress and dull eyes. Ketosis also affected on pathological part which characterized by fatty liver. In this review, we are focusing various key aspects of the disease with special reference on the clinical, biochemical and histological changes during development of pregnancy ketosis in goat population.